Pengaruh Lingkungan Kerja dan Kompensasi Terhadap Kinerja Pegawai Pada Dinas Pemuda dan Olahraga Provinsi DKI Jakarta Tahun 2016 - Pujiati, Herni; Nabilah, Lily (Universitas Mohammad Husni Thamrin, 2020)
The Effect Of Work Environment And Compensation To Employee Performance On The Office Of Youth And Sports Dki Jakarta. Based on the results of this study explains that the influence of Work Environment on the performance of employees from the results of research values obtained Work Environment significantly influence Employee performance. The results of this study are supported by previous research conducted by Sugiarti (2012), Ferry Setiawan (2012), and I Putu Sedhana (2012) which said that the Work Environment has a significant positive effect on employee performance. Based on the results of this study explains that the influence of compensation on the performance of employees from the results of compensation research has a significant effect on employee performance. The results of this study are supported by previous research conducted by Wayan Niko Susanta (2013), Agiel Puji Damayanti (2013) which said that Compensation has a significant positive effect on employee performance. Based on the results of this study explained that the Work Environment and Compensation have a positive effect on the performance of employees from the results of research values obtained Work Environment and Compensation positively and significantly affect the performance of employees. The results of this study are supported by previous research conducted by Sugiarti (2012), Ferry Setiawan (2012), and I Putu Sedhana (2012) which said that the Work Environment has a significant positive effect on Employee performance, and this research is supported by previous research conducted by Wayan Niko Susanta (2013), Agiel Puji Damayanti (2013) who said that organizational commitment has a significant positive effect on employee performance. Based on the results of the above research and previous research and the results of the coefficient of determination as a whole can be concluded that the variables Work Environment and Compensation has a positive and significant impact on the performance of Employees On DKI Jakarta Youth and Sports Office.